An investigation into assessing speaking of students learning new English textbook in a high school in Vietnam - Trần, Thị Hiền (2020)
Language assessment in general and oracy assessment in particular has posed language teachers high schools in Vietnam many troubles. One of the outstanding issues relate to the design of speaking activities that saw poorly, boring tasks that do not motivate learners while learning the skill. The other issue refers to the assessing criteria that are not familiarized by language teachers at schools. This research aims at finding popular task types that teachers used when assessing speaking. Also, the study provides a framework for speaking assessment criteria that can be applicable for teachers as well as problems encountered by teachers when doing speaking assessment. The study was carried out with 5 teachers of English at a school in Hai Duong. The results reveal a fact that most teachers are not familiar with task types neither assessment criteria. Last but not least, the researcher would like to suggest some changes in teaching English at schools so that students can balance among language skills and aspects.